TRAINING MORALLY MATURE AND SELFLESS OFFICIALS IS AN IMPORTANT FACTOR IN THE COUNTRY'S DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
The article highlights opinions on the rules of conduct, rights, duties, peculiarities of public officials and on the formation of the legal framework coordinating their activities, on the importance of applying in practice the rules formulated on the basis of national management traditions inherent in our spiritual values.